Antibacterial Activity of 1-[(2,4-Dichlorophenethyl)amino]-3-Phenoxypropan-2-ol against Antibiotic-Resistant Strains of Diverse Bacterial Pathogens, Biofilms and in Pre-clinical Infection Models - Defraine, Valerie; Verstraete, Laure; Van Bambeke, Françoise; Anantharajah, Ahalieyah; Townsend, Eleanor M.; Ramage, Gordon; Corbau, Romu; Marchand, Arnaud; Chaltin, Patrick; Fauvart, Maarten; Michiels, Jan (Frontiers in Microbiology, 2017)
We recently described the novel anti-persister compound 1-((2,4-dichlorophenethyl)amino)-3-phenoxypropan-2-ol (SPI009), capable of directly killing persister cells of the Gram-negative pathogen Pseudomonas aeruginosa. This compound also shows antibacterial effects against non-persister cells, suggesting that SPI009 could be used as an adjuvant for antibacterial combination therapy. Here, we demonstrate the broad-spectrum activity of SPI009, combined with different classes of antibiotics, against the clinically relevant ESKAPE pathogens Enterobacter aerogenes, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, P. aeruginosa, Enterococcus faecium and Burkholderia cenocepacia and Escherichia coli. Importantly, SPI009 re-enabled killing of antibiotic-resistant strains and effectively lowered the required antibiotic concentrations. The clinical potential was further confirmed in biofilm models of P. aeruginosa and S. aureus where SPI009 exhibited effective biofilm inhibition and eradication. Caenorhabditis elegans infected with P. aeruginosa also showed a significant improvement in survival when SPI009 was added to conventional antibiotic treatment. Overall, we demonstrate that SPI009, initially discovered as an anti-persister molecule in P. aeruginosa, possesses broad-spectrum activity and is highly suitable for the development of antibacterial combination therapies in the fight against chronic infections.